Capacity Building for Animal Science Students in Judging Aspects of Garut Sheep Contests - Nurmeidiansyah, An An; Heriyadi, Denie; Alhuur, Ken Ratu gharizah (Unpad Press, 2026)
Livestock evaluation is an inseparable component of the selection process. Students enrolled in study programs related to animal science must have a good command of the key aspects that serve as important criteria in livestock judging. This issue becomes particularly relevant, given the fact that many students often still experience confusion when they are directly involved applied practice as livestock evaluators or judges. This factual condition indicates they need for capacity-building programs that are not only educational, but also practical and applicable in the operational practice. One simple and effective method of information delivery is through socialization activities, followed by discussions and applied practice. This Community Service Activity (PKM) was conducted at the Faculty of Animal Science, Universitas Padjadjaran, targeting students who participated in the Indonesian Animal Science Student Scientific Meeting (TIMPI) on September 3, 2023. Based on the results of the pretest and posttest, it was revealed that prior to the delivery of the material (socialization), some participants already possessed knowledge and understanding of sheep judging; however, the majority of participants lacked knowledge and understanding regarding the distinctive characteristics of Garut sheep and sheep age estimation. Overall, this activity successfully improved participants knowledge and understanding of the aspects used as criteria in livestock evaluation, particularly those related to judging, the distinctive characteristics of Garut sheep, and sheep age estimation. Nevertheless, despite the observed improvement in knowledge and understanding, continuous mentoring is still required to prepare students to become the next generation of judges in livestock contests within their respective regions.